The Potential of Centella asiatica Herb and Cyperus rotundus L. Rhizomes Extract as a Chemoprevention Agent for Lung Cancer - Indrayanti, Indrayanti; Hidayati, Titiek; Setyanto, Arif B. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The number of smokers is increasing in Indonesia. Cigarette smoke can cause many diseases, such as lung cancer. Centella asiatica (CAS) and Cyperus rotundus L. rhizomes (CRR) exhibit anti-cancer effects. AIM: The study examined the cytotoxic effects of CRR and CAS extracts in lung cancer cells. METHODOLOGY: This research used the maceration method to extract the CAS and CRR powder and methanol solvent. Extraction was tested at 600μl, 400μl, 200 μl, 100 μl, and 50 μl to determine the effect of compound cytotoxicity causing 50% cell death or IC50. Cytotoxicity tests used the MTT method to obtain purple formation crystals and used an ELISA reader to obtain absorbance values. RESULTS: CRR and CAS extract shows a low cytotoxicity effect. IC50 of CRR and CAS methanol extracts was 235 μg/ml and 279 μg/ml, respectively. CONCLUSION: CRR and CAS extracts were proven to show chemopreventive activities against lung cancer cells.